Liquid-liquid phase separation in chromatin - Rippe, Karsten (Cold Spring Harbor perspectives in biology, 2022)
In eukaryotic cells, protein and RNA factors involved in genome activities like transcription, RNA processing, DNA replication, and repair accumulate in self-organizing membraneless chromatin subcompartments. These structures contribute to efficiently conduct chromatin-mediated reactions and to establish specific cellular programs. However, the underlying mechanisms for their formation are only partly understood. Recent studies invoke liquid-liquid phase separation (LLPS) of proteins and RNAs in the establishment of chromatin activity patterns. At the same time, the folding of chromatin in the nucleus can drive genome partitioning into spatially distinct domains. Here, the interplay between chromatin organization, chromatin binding, and LLPS is discussed by comparing and contrasting three prototypical chromatin subcompartments: the nucleolus, clusters of active RNA polymerase II, and pericentric heterochromatin domains. It is discussed how the different ways of chromatin compartmentalization are linked to transcription regulation, the targeting of soluble factors to certain parts of the genome, and to disease-causing genetic aberrations.